ANALISIS MAKNA MAJAS METONIMIA PADA DRAMA JEPANG 35 SAI NO KOUKOUSEI - Annisaturahmi Annisaturahmi; Sri Wahyu Widiati; Arza Aibonotika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstarct: This study is about metonymy in the drama 35 Sai No Koukousei. The purpose of this study was to explain the use of metonymy type in the drama 35 Sai no Koukousei. This study uses an example based method. The results show that metonymy in dorama 35 Sai No Koukousei has many variations in relationship of proximity of time and space, and form of metonymy.Keywords : metonymy, example based method, time and space proximity